2016
DOI: 10.1007/s10895-016-2005-y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective and Sensitive Colorimetric and Fluorescent Chemosensor for Rapid Detection of Ag+, Cu2+ and Hg2+ Based on a Simple Schiff Base

Abstract: A new reversible colorimetric and fluorescent chemosensor MMIP based on a simple Schiff base has been successfully synthesized. MMIP exhibited high selectivity and sensitivity towards Ag, Cu and Hg ions with a short response time in DMSO/HO (1/1, v/v) solution among various metal ions, and the results could be monitored directly by naked eyes. The binding stoichiometry between MMIP and Ag/Hg/Cu has been determined to be 1:2 by Job's plot and FT-IR analysis. MMIP could effectively detect Ag, Cu and Hg over a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…To determine the nature of the sample between surface of electrode and Hg 2+ , Ag + and Cu 2+ , FT-IR spectra of platinum nanoparticle electrode was recorded in the presence of Hg 2+ , Ag + and Cu 2+ (Figure 8). The findings showed that the metal ion Hg 2+ , Ag + and Cu 2+ was in perfect harmony with the nanoparticulate surface Pt, and the literature published [25].…”
Section: Resultsmentioning
confidence: 64%
“…To determine the nature of the sample between surface of electrode and Hg 2+ , Ag + and Cu 2+ , FT-IR spectra of platinum nanoparticle electrode was recorded in the presence of Hg 2+ , Ag + and Cu 2+ (Figure 8). The findings showed that the metal ion Hg 2+ , Ag + and Cu 2+ was in perfect harmony with the nanoparticulate surface Pt, and the literature published [25].…”
Section: Resultsmentioning
confidence: 64%
“…To meet the demand of colorimetric sensors that can detect easily and rapidly copper, we designed the chemosensor APTS (Scheme 1), which contains sulphur in its structure. Sulphur is well known to have a high affinity to Cu 2+ , Ag + and Hg 2+ , and a number of sulphur‐containing sensors have been reported to detect the three metals . In order to selectively detect only Cu 2+ among them, we endowed the sensor APTS with a hard character by using moieties with nitrogen and oxygen atoms .…”
Section: Introductionmentioning
confidence: 99%
“…Sulphur is well known to have a high affinity to Cu 2+ , Ag + and Hg 2+ , and a number of sulphur-containing sensors have been reported to detect the three metals. [29][30][31][32] In order to selectively detect only Cu 2+ among them, we endowed the sensor APTS with a hard character by using moieties with nitrogen and oxygen atoms. [33][34][35][36] As expected, the sensor APTS detected only Cu 2+ via the colour change from colourless to yellow.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of optical chemical sensors were reported which operated based on absorbance, florescence or luminescence. In these optodes, indicator molecules due to changing analyte concentration product a signal proportional with analyte amount, accordingly detection and determination of different molecules as well as ions …”
Section: Introductionmentioning
confidence: 99%